Highly compacted lithium iron phosphate cathode material and preparation method thereof
Patent Information
- Application Number
- CN202611320126.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]针对现有技术的不足,本发明提供一种高压实磷酸铁锂正极材料及其制备方法,解决现有高压实磷酸铁锂正极材料通过扩大颗粒尺寸差异提高颗粒填充程度时,容易出现部分颗粒过度长大和部分颗粒生长不足,使粉末压实密度与容量发挥、倍率性能难以兼顾的问题
1、本申请采用比表面积不同的第一磷酸铁和第二磷酸铁,使两者具有不同的晶粒生长趋势,并使由葡萄糖和聚乙烯醇组成的第一碳源与第一磷酸铁对应、以葡萄糖作为第二碳源与第二磷酸铁对应,通过对第一磷酸铁较强的晶粒生长趋势进行针对性限制,同时避免对第二磷酸铁施加相同程度的晶粒生长限制,使两类磷酸铁在高温烧结阶段形成受控的颗粒尺寸差异,减少异常粗颗粒和过细颗粒的形成,从而在提高粉末压实密度的同时保持容量发挥和倍率性能。
Smart Images

Figure CN122977341A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery cathode material technology, specifically to a high-pressure lithium iron phosphate cathode material and its preparation method. Background Technology
[0002] Lithium iron phosphate (LFP) cathode materials exhibit good cycle stability and thermal stability, making them suitable for use in lithium-ion batteries. With increasing energy density requirements for lithium-ion batteries, improving the powder compaction density of LFP cathode materials has become a crucial approach to increasing the active material content per unit volume. Existing technologies typically achieve different particle size distributions in LFP particles by adjusting the characteristics of the LFP raw material, changing the slurry grinding particle size, constructing particle gradation, adjusting the carbon source, and altering sintering conditions, thereby improving the degree of particle packing.
[0003] When existing high-compaction lithium iron phosphate cathode materials increase particle filling density by expanding particle size differences, some particles tend to grow excessively while others grow insufficiently, resulting in an imbalance between the ratio of coarse and fine particles. This makes it difficult to maintain both the capacity and rate performance of the lithium iron phosphate cathode material when the powder compaction density is further increased. Summary of the Invention
[0004] To address the shortcomings of existing technologies, this invention provides a high-compaction lithium iron phosphate cathode material and its preparation method. This solves the problem that existing high-compaction lithium iron phosphate cathode materials, when increasing particle size differences to improve particle filling, often result in some particles growing excessively and others growing insufficiently, making it difficult to simultaneously achieve powder compaction density, capacity utilization, and rate performance.
[0005] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a high-pressure lithium iron phosphate cathode material, comprising the following steps: S1 uses a specific surface area of 12.0–18.0 m². 2 / g of primary ferric phosphate and a specific surface area of 4.0–8.0 m² 2 / g of second iron phosphate; the first carbon source is composed of glucose and polyvinyl alcohol, and the second carbon source is glucose; the first iron phosphate and the polyvinyl alcohol are premixed and then a lithium source and glucose from the first carbon source are added, and the mixture is wet-milled to obtain a first precursor slurry; the second iron phosphate, lithium source, second carbon source and deionized water are mixed and wet-milled to obtain a second precursor slurry, and the median particle size difference between the first precursor slurry and the second precursor slurry is not greater than 0.04 μm; S2, the first precursor slurry and the second precursor slurry are spray-dried respectively to obtain the first spray precursor and the second spray precursor; S3, the first spray precursor and the second spray precursor are mixed to obtain a mixed precursor. Under nitrogen protection, the mixed precursor is subjected to a low-temperature carbonization stage and a high-temperature sintering stage in sequence. The temperature of the low-temperature carbonization stage is 400-450°C, and the temperature of the high-temperature sintering stage is 740-770°C. After cooling, the high-pressure lithium iron phosphate cathode material is obtained.
[0006] Furthermore, the Fe / P molar ratio of both the first and second iron phosphates is 0.995–1.005, and the median particle size of both raw materials is 0.8–1.8 μm.
[0007] Furthermore, the mass ratio of glucose to polyvinyl alcohol in the first carbon source is 65:35 to 80:20, the amount of the first carbon source added is 6.0% to 8.0% of the mass of the first iron phosphate, and the amount of the second carbon source added is 6.0% to 8.0% of the mass of the second iron phosphate.
[0008] Furthermore, the lithium source is lithium carbonate, and the Li / Fe molar ratio in the first precursor slurry and the second precursor slurry is 1.02 to 1.05.
[0009] Furthermore, the median particle size of both the first precursor slurry and the second precursor slurry is 0.30–0.40 μm.
[0010] Furthermore, the degree of alcoholysis of the polyvinyl alcohol is 87-89 mol%, and the degree of polymerization is 1600-1800.
[0011] Furthermore, the inlet air temperature of the spray dryer is 210–240°C, and the outlet air temperature is 90–110°C; based on the mass of the iron phosphate contained, the mass ratio of the first spray precursor to the second spray precursor is 55:45–65:35.
[0012] Furthermore, the low-temperature carbonization stage lasts for 2 to 4 hours, and the high-temperature sintering stage lasts for 7 to 10 hours.
[0013] Furthermore, after the high-temperature sintering stage is completed, the material is cooled under nitrogen protection, and then subjected to airflow pulverization and sieving.
[0014] This application also provides a high-compaction lithium iron phosphate cathode material, wherein the high-compaction lithium iron phosphate cathode material has a D10 of 0.61–0.68 μm, a median particle size of 1.68–1.90 μm, a D90 of 4.50–5.14 μm, a carbon content of 1.31–1.46 wt%, and a powder compaction density measured at 100 MPa for 10 s is 2.69–2.74 g / cm³. 3 .
[0015] This invention provides a high-pressure lithium iron phosphate cathode material and its preparation method. It has the following beneficial effects: 1. This application uses first ferric phosphate and second ferric phosphate with different specific surface areas, so that the two have different grain growth trends. The first carbon source composed of glucose and polyvinyl alcohol corresponds to the first ferric phosphate, and the second carbon source composed of glucose corresponds to the second ferric phosphate. By specifically restricting the strong grain growth trend of the first ferric phosphate, while avoiding applying the same degree of grain growth restriction to the second ferric phosphate, the two types of ferric phosphate form a controlled particle size difference during the high-temperature sintering stage, reducing the formation of abnormal coarse particles and excessively fine particles. Thus, while improving the compaction density of the powder, the capacity utilization and rate performance are maintained.
[0016] 2. This application controls the median particle size difference between the first precursor slurry and the second precursor slurry to no more than 0.04 μm, so that the two precursor slurries maintain similar median particle sizes before sintering. The final particle size difference is mainly formed by the different grain growth trends of the first iron phosphate and the second iron phosphate, as well as the differential adjustment of the first carbon source and the second carbon source, thereby reducing the direct impact of the pre-gradation of large and small particles before sintering on the final particle distribution.
[0017] 3. In this application, the first precursor slurry and the second precursor slurry are spray-dried separately and then mixed, so that the local correspondence between the first iron phosphate and the first carbon source and the second iron phosphate and the second carbon source is maintained before common high-temperature sintering. The test results show that compared with mixing the two precursor slurries first and then spray-drying them together, spray-drying them separately can further improve the powder compaction density and 3C discharge specific capacity.
[0018] 4. This application sequentially processes the mixed precursor through a low-temperature carbonization stage and a high-temperature sintering stage, allowing the first and second carbon sources to undergo pyrolysis carbonization first, followed by high-temperature sintering of lithium iron phosphate. A powder compaction density of 2.69–2.74 g / cm³ is obtained within the corresponding temperature and time range. 3 High-pressure lithium iron phosphate cathode material. Attached Figure Description
[0019] Figure 1 This is a flowchart illustrating the preparation process of the high-pressure lithium iron phosphate cathode material in this application; Figure 2 This is a schematic diagram illustrating the adjustment relationship between the first and second iron phosphates and their corresponding carbon sources in this application. Figure 3 This is a comparison chart of powder compaction density and 3C discharge specific capacity for Embodiment 2 and Comparative Examples 1 to 6 of this application. Detailed Implementation
[0020] The present application will be further described in detail below with reference to the embodiments.
[0021] Lithium iron phosphate (LFP) cathode materials exhibit good cycle stability and safety performance. Increasing the powder compaction density of LFP cathode materials is beneficial for increasing the content of active material per unit volume. Existing high-compaction LFP cathode materials typically improve powder compaction density by adjusting the particle size of iron phosphate raw materials, using precursors of different particle sizes, or performing particle gradation after sintering to allow particles of different sizes to fill each other. However, when increasing particle packing density by expanding particle size differences, some particles may become excessively large while others are undergrown during sintering. Excessively large particles increase the diffusion distance of lithium ions, while an increased proportion of excessively fine particles increases the specific surface area and the number of interparticle interfaces. Therefore, further increasing the powder compaction density can negatively impact the material's capacity utilization and rate performance.
[0022] Based on the above problems, this application studied the sintering process of different ferric phosphates under the same grinding particle size conditions. It was found that when the first ferric phosphate and the second ferric phosphate have different specific surface areas, even when the first precursor slurry and the second precursor slurry are ground to similar median particle sizes, they still exhibit different grain growth trends in the subsequent high-temperature sintering stage. Specifically, the first ferric phosphate, with its higher specific surface area, exhibits a stronger grain growth trend, while the second ferric phosphate, with its lower specific surface area, shows a relatively weaker grain growth trend. If sintering is carried out solely based on these differences, the particles formed by the first ferric phosphate tend to grow excessively, while the particles formed by the second ferric phosphate remain relatively small, resulting in a final particle size distribution that expands towards both ends, and failing to stably obtain a particle distribution suitable for high-pressure compaction.
[0023] Further research revealed that setting the first carbon source as a combination of glucose and polyvinyl alcohol, and premixing the first ferric phosphate with the polyvinyl alcohol aqueous solution before adding the lithium source and glucose, allows the polyvinyl alcohol to preferentially distribute around the first ferric phosphate. Simultaneously, setting the second carbon source as glucose prevents the second ferric phosphate from being subject to the same degree of grain growth limitation as the first ferric phosphate. Based on this, spray drying the first and second precursor slurries separately yields a first spray precursor and a second spray precursor. Mixing the first and second spray precursors maintains the correspondence between the first carbon source and the first ferric phosphate, and between the second carbon source and the second ferric phosphate, before heat treatment.
[0024] Subsequently, a low-temperature carbonization stage is used to establish the first and second carbon sources in their respective precursors, and then a high-temperature sintering stage is used to induce lithiation and grain growth in the first and second iron phosphates. The strong grain growth tendency of the first iron phosphate is limited by the localized grain growth formed by polyvinyl alcohol in the first carbon source, while the grain growth tendency of the second iron phosphate is weaker. Using a second carbon source without polyvinyl alcohol can maintain moderate grain growth, thereby compensating for the original grain growth differences between the two iron phosphates, reducing the formation of abnormally coarse and excessively fine particles. This results in a high-pressure lithium iron phosphate cathode material with a suitable particle size distribution without relying on significant pre-gradation of large and small particle sizes before sintering. This application is based on the above findings. The preparation process of the high-pressure lithium iron phosphate cathode material of this application is as follows: Figure 1 As shown, the adjustment relationships between the first ferric phosphate, the second ferric phosphate, and their corresponding carbon sources are as follows: Figure 2 As shown.
[0025] The main experimental materials used in the embodiments of this application are as follows.
[0026] Both the first and second ferric phosphates are battery-grade anhydrous ferric phosphates with the chemical formula FePO4, CAS number 10045-86-0, and a purity of not less than 99.5%. The first and second ferric phosphates have different specific surface areas, and the specific specific surface areas are selected according to each embodiment.
[0027] The lithium source is battery-grade lithium carbonate with the chemical formula Li2CO3, CAS number 554-13-2, and a purity of not less than 99.5%.
[0028] The first carbon source consists of glucose and polyvinyl alcohol. The glucose used is anhydrous D-glucose, with the chemical formula C6H2O. 12 O6, CAS number 50-99-7, purity not less than 99%; polyvinyl alcohol, CAS number 9002-89-5, degree of alcoholysis 87-89 mol%, degree of polymerization 1600-1800.
[0029] The second carbon source is anhydrous D-glucose, with the chemical formula C6H2O. 12 O6, CAS number 50-99-7, purity not less than 99%.
[0030] The water used for slurry preparation is deionized water, CAS number 7732-18-5.
[0031] Nitrogen is used as a protective gas during the low-temperature carbonization stage, the high-temperature sintering stage, and the cooling process. The CAS number of nitrogen is 7727-37-9, and its purity is not less than 99.999%.
[0032] Unless otherwise stated, all experimental materials mentioned above can be commercially available products that meet the purity and specifications requirements.
[0033] Example 1 Weigh out 600 g of ferric phosphate, whose specific surface area is 12.0 m². 2 / g, Fe / P molar ratio is 1.000, median particle size of raw material is 1.21 μm; 400 g of ferric phosphate was weighed, its specific surface area is 6.1 m². 2 / g, Fe / P molar ratio is 1.001, and median particle size of raw material is 1.18 μm.
[0034] In this embodiment, the Li / Fe molar ratio is 1.02. For the first ferric phosphate, 149.9 g of lithium carbonate was added, and for the second ferric phosphate, 99.9 g of lithium carbonate was added.
[0035] The amount of the first carbon source added is 7.0% of the mass of the first iron phosphate. The mass ratio of glucose to polyvinyl alcohol in the first carbon source is 70:30. Therefore, 29.4 g of glucose and 12.6 g of polyvinyl alcohol are added.
[0036] First, prepare a polyvinyl alcohol aqueous solution according to the aforementioned method, then add ferric phosphate for premixing, then add 149.9 g of lithium carbonate and 29.4 g of glucose, add deionized water and perform wet sand milling to obtain a first precursor slurry with a median particle size of 0.30 μm.
[0037] The second carbon source was added at 7.0% of the mass of the second ferric phosphate, therefore 28.0 g of glucose was added. The second ferric phosphate, 99.9 g of lithium carbonate, 28.0 g of glucose, and deionized water were mixed and wet-milled to obtain a second precursor slurry with a median particle size of 0.34 μm. The difference in median particle size between the two precursor slurries was 0.04 μm.
[0038] The first precursor slurry and the second precursor slurry were spray-dried separately. The inlet air temperature for spray drying was 225°C and the outlet air temperature was 100°C.
[0039] Since the feed masses of the first and second ferric phosphates are 600 g and 400 g respectively, the mass ratio of the first spray precursor to the second spray precursor is 60:40 based on the ferric phosphate content. The two are mixed for 30 min to obtain the mixed precursor.
[0040] Under nitrogen protection, the temperature was increased to 400℃ at 3℃ / min and held for 4 hours to complete the low-temperature carbonization stage; then the temperature was increased to 755℃ at 3℃ / min and held for 8 hours to complete the high-temperature sintering stage.
[0041] After sintering, the material is cooled to below 100°C under nitrogen protection, removed, and then subjected to airflow pulverization and sieving to obtain high-pressure lithium iron phosphate cathode material.
[0042] Example 2 Weigh out 600 g of ferric phosphate, whose specific surface area is 15.1 m². 2 / g, Fe / P molar ratio is 0.999, median particle size of raw material is 1.25 μm; 400 g of ferric phosphate was weighed, its specific surface area is 6.0 m². 2 / g, Fe / P molar ratio is 1.002, and median particle size of raw material is 1.21 μm.
[0043] The Li / Fe molar ratio is 1.03. For the first ferric phosphate, 151.4 g of lithium carbonate was added, and for the second ferric phosphate, 100.9 g of lithium carbonate was added.
[0044] The amount of the first carbon source added is 7.0% of the mass of the first iron phosphate, wherein the mass ratio of glucose to polyvinyl alcohol is 70:30, therefore 29.4 g of glucose and 12.6 g of polyvinyl alcohol are added.
[0045] Following the aforementioned method, first, ferric phosphate and polyvinyl alcohol are premixed, then 151.4 g of lithium carbonate and 29.4 g of glucose are added, and the mixture is wet-milled until the median particle size is 0.33 μm to obtain the first precursor slurry.
[0046] The second carbon source is glucose, added at 7.0% of the mass of the second ferric phosphate, i.e., 28.0 g. The second ferric phosphate, 100.9 g of lithium carbonate, 28.0 g of glucose and deionized water are mixed and wet-milled to obtain a second precursor slurry with a median particle size of 0.35 μm.
[0047] The median particle size difference between the two precursor slurries was 0.02 μm.
[0048] Spray drying was performed separately, with an inlet air temperature of 225℃ and an outlet air temperature of 100℃, to obtain the first spray precursor and the second spray precursor.
[0049] Based on the mass conversion of iron phosphate, the first spray precursor and the second spray precursor are mixed at a mass ratio of 60:40.
[0050] Under nitrogen protection, the temperature was raised to 420℃ and held for 3 hours to complete the low-temperature carbonization stage; then the temperature was raised to 755℃ and held for 8 hours to complete the high-temperature sintering stage.
[0051] After cooling, the material is pulverized and sieved by airflow to obtain high-pressure lithium iron phosphate cathode material.
[0052] Example 3 Weigh out 600 g of ferric phosphate, whose specific surface area is 18.0 m². 2 / g, Fe / P molar ratio is 0.998, median particle size of raw material is 1.30 μm; 400 g of ferric phosphate was weighed, its specific surface area is 6.0 m². 2 / g, Fe / P molar ratio is 1.002, and median particle size of raw material is 1.24 μm.
[0053] The Li / Fe molar ratio is 1.04. For the first ferric phosphate, 152.9 g of lithium carbonate is added, and for the second ferric phosphate, 101.9 g of lithium carbonate is added.
[0054] The amount of the first carbon source added is 7.0% of the mass of the first iron phosphate. The mass ratio of glucose to polyvinyl alcohol in the first carbon source is 70:30, corresponding to the addition of 29.4 g of glucose and 12.6 g of polyvinyl alcohol.
[0055] The first precursor slurry was prepared according to the aforementioned method and milled to a median particle size of 0.36 μm.
[0056] The second carbon source is glucose, which is added at 7.0% of the mass of the second iron phosphate, i.e., 28.0 g. The second precursor slurry is prepared according to the aforementioned method and milled to a median particle size of 0.40 μm.
[0057] The median particle size difference between the two precursor slurries was 0.04 μm.
[0058] Spray drying was performed separately, with an inlet air temperature of 225℃ and an outlet air temperature of 100℃.
[0059] Based on the mass conversion of iron phosphate, the first spray precursor and the second spray precursor are mixed at a mass ratio of 60:40.
[0060] Under nitrogen protection, the temperature was raised to 450℃ and held for 2 hours to complete the low-temperature carbonization stage; then the temperature was raised to 755℃ and held for 8 hours to complete the high-temperature sintering stage.
[0061] After cooling, the material is pulverized and sieved by airflow to obtain high-pressure lithium iron phosphate cathode material.
[0062] Example 4 Weigh out 550 g of ferric phosphate, whose specific surface area is 15.0 m². 2 / g, Fe / P molar ratio is 0.999, median particle size of raw material is 1.23 μm; 450 g of ferric phosphate was weighed, its specific surface area is 8.0 m². 2 / g, Fe / P molar ratio is 1.003, and median particle size of raw material is 1.20 μm.
[0063] The Li / Fe molar ratio is 1.03. For the first ferric phosphate, 138.8 g of lithium carbonate was added, and for the second ferric phosphate, 113.5 g of lithium carbonate was added.
[0064] The amount of the first carbon source added is 6.0% of the mass of the first iron phosphate, totaling 33.0 g. The mass ratio of glucose to polyvinyl alcohol is 80:20, corresponding to the addition of 26.4 g of glucose and 6.6 g of polyvinyl alcohol.
[0065] The first precursor slurry was prepared according to the aforementioned method, with a median particle size of 0.34 μm.
[0066] The second carbon source is glucose, which is added at 6.0% of the mass of the second iron phosphate, i.e., 27.0 g, to prepare a second precursor slurry with a median particle size of 0.36 μm.
[0067] The median particle size difference between the two precursor slurries was 0.02 μm.
[0068] Spray drying was performed separately, with an inlet air temperature of 210℃ and an outlet air temperature of 90℃.
[0069] Based on the mass conversion of iron phosphate, the first spray precursor and the second spray precursor were mixed at a mass ratio of 55:45.
[0070] Under nitrogen protection, the temperature was raised to 420℃ and held for 3 hours to complete the low-temperature carbonization stage; then the temperature was raised to 740℃ and held for 10 hours to complete the high-temperature sintering stage.
[0071] After cooling, the material is pulverized and sieved by airflow to obtain high-pressure lithium iron phosphate cathode material.
[0072] Example 5 Weigh out 650 g of ferric phosphate, whose specific surface area is 15.2 m². 2 / g, Fe / P molar ratio is 0.997, median particle size of raw material is 1.28 μm; 350 g of ferric phosphate was weighed, its specific surface area is 4.0 m². 2 / g, Fe / P molar ratio is 1.004, and median particle size of raw material is 1.22 μm.
[0073] The Li / Fe molar ratio is 1.05. For the first ferric phosphate, 167.2 g of lithium carbonate was added; for the second ferric phosphate, 90.0 g of lithium carbonate was added.
[0074] The amount of the first carbon source added is 8.0% of the mass of the first iron phosphate, totaling 52.0 g. The mass ratio of glucose to polyvinyl alcohol is 65:35, corresponding to the addition of 33.8 g of glucose and 18.2 g of polyvinyl alcohol.
[0075] The first precursor slurry was prepared according to the aforementioned method, wherein the endpoint of the wet sand milling was specifically controlled so that the median particle size of the first precursor slurry was 0.32 μm.
[0076] The second carbon source is glucose, which is added at 8.0% of the mass of the second iron phosphate, i.e., 28.0 g. The median particle size of the resulting second precursor slurry is 0.35 μm.
[0077] The median particle size difference between the two precursor slurries was 0.03 μm.
[0078] Spray drying was performed separately, with an inlet air temperature of 240℃ and an outlet air temperature of 110℃.
[0079] Based on the mass conversion of iron phosphate, the first spray precursor and the second spray precursor were mixed at a mass ratio of 65:35.
[0080] Under nitrogen protection, the temperature was raised to 420℃ and held for 3 hours to complete the low-temperature carbonization stage; then the temperature was raised to 770℃ and held for 7 hours to complete the high-temperature sintering stage.
[0081] After cooling, the material is pulverized and sieved by airflow to obtain high-pressure lithium iron phosphate cathode material.
[0082] Comparative Example 1 Based on Example 2, only the difference in specific surface area between the first ferric phosphate and the second ferric phosphate was eliminated.
[0083] Both primary and secondary ferric phosphates use a specific surface area of 6.0 m². 2 The same batch of iron phosphate with a weight of / g was subjected to the same feeding mass, Fe / P molar ratio, lithium source, first carbon source, second carbon source, median particle size of first precursor slurry and second precursor slurry, spray drying, mixing ratio, low-temperature carbonization stage and high-temperature sintering stage as in Example 2.
[0084] The obtained materials serve as Comparative Example 1.
[0085] Comparative Example 2 Based on Example 2, only the second carbon source was changed.
[0086] The first carbon source remains unchanged. The second carbon source is changed from glucose to a combination of glucose and polyvinyl alcohol, with a mass ratio of glucose to polyvinyl alcohol of 70:30. The total amount of the second carbon source added is still 7.0% of the mass of the second iron phosphate.
[0087] When preparing the second precursor slurry, the same method as for the first precursor slurry is used: first, the second ferric phosphate is premixed with polyvinyl alcohol, and then lithium carbonate and glucose are added.
[0088] All other conditions are the same as in Example 2.
[0089] The obtained materials serve as Comparative Example 2.
[0090] Comparative Example 3 Based on Example 2, only the correspondence between the first carbon source and the second carbon source and the two types of iron phosphate is reversed.
[0091] The first carbon source corresponding to the first ferric phosphate is changed to glucose, and the total amount added is still 7.0% of the mass of the first ferric phosphate.
[0092] The second carbon source for the second ferric phosphate is changed to a combination of glucose and polyvinyl alcohol, with the total amount added still being 7.0% of the mass of the second ferric phosphate, wherein the mass ratio of glucose to polyvinyl alcohol is 70:30.
[0093] The second ferric phosphate is premixed with polyvinyl alcohol before lithium carbonate and glucose are added; the first ferric phosphate is not premixed with polyvinyl alcohol.
[0094] All other conditions are the same as in Example 2.
[0095] The obtained materials serve as Comparative Example 3.
[0096] Comparative Example 4 The first precursor slurry and the second precursor slurry were prepared according to the method of Example 2, and achieved median particle sizes of 0.33 μm and 0.35 μm, respectively.
[0097] The only difference lies in the spray treatment method.
[0098] Instead of spray drying the first precursor slurry and the second precursor slurry separately, the first precursor slurry and the second precursor slurry are first mixed in a ratio of 60:40 of the mass of iron phosphate contained therein, and then the resulting mixed slurry is spray dried once.
[0099] The inlet air temperature for spray drying is 225℃, and the outlet air temperature is 100℃.
[0100] The resulting spray precursor was further processed according to the low-temperature carbonization stage and high-temperature sintering stage of Example 2.
[0101] The obtained materials serve as Comparative Example 4.
[0102] Comparative Example 5 Based on Example 2, only the polyvinyl alcohol in the first carbon source was removed.
[0103] The first carbon source is changed to glucose, and the amount added is still 7.0% of the mass of the first ferric phosphate; the second carbon source remains glucose, and the amount added is still 7.0% of the mass of the second ferric phosphate.
[0104] The remaining raw materials, slurry particle size, spray drying, mixing ratio, low-temperature carbonization stage and high-temperature sintering stage are the same as in Example 2.
[0105] The obtained materials serve as Comparative Example 5.
[0106] Comparative Example 6 Based on Example 2, only the mass ratio of glucose to polyvinyl alcohol in the first carbon source was changed.
[0107] The total amount of the first carbon source added remains 7.0% of the mass of the first iron phosphate, but the mass ratio of glucose to polyvinyl alcohol is adjusted to 50:50.
[0108] The second carbon source and all other process conditions are the same as in Example 2.
[0109] The obtained materials serve as Comparative Example 6.
[0110] Test Example 1 The particle size distribution and powder compaction density of the high-compact lithium iron phosphate cathode materials obtained in Examples 1 to 5 and Comparative Examples 1 to 6 were tested respectively.
[0111] Particle size was determined using a laser particle size analyzer, with deionized water as the dispersion medium, and D10, median particle size, and D90 were tested under the same ultrasonic dispersion conditions.
[0112] The compacted powder density was tested using a cylindrical powder mold. 0.50 g of sample was weighed and added to a mold with an inner diameter of 13 mm, and held at 100 MPa for 10 s. The compacted powder density was calculated based on the mass and volume of the compacted sample. Each sample was tested in triplicate, and the average value was taken.
[0113] The test results are shown in Table 1 and Figure 3 .
[0114] Table 1. Particle size distribution and powder compaction density test results for each example and comparative example.
[0115] As shown in Table 1, the powder compaction density of the high-pressure lithium iron phosphate cathode materials obtained in Examples 1 to 5 all reached 2.69 g / cm³. 3 In addition, D10 and D90 maintain a moderate particle size range, without any obvious excessive expansion towards the coarse or fine particle ends.
[0116] Compared with Comparative Example 1, in Example 2, with the configuration of the first and second carbon sources remaining unchanged, the difference in specific surface area between the first and second ferric phosphates was eliminated, and the powder compaction density increased from 2.74 g / cm³. 3 Reduced to 2.61 g / cm³3 This indicates that the different grain growth trends between primary ferric phosphate and secondary ferric phosphate are the basis for forming a particle size distribution suitable for improving particle filling efficiency.
[0117] Compared with Comparative Example 2, in Example 2, when the second ferric phosphate also used a carbon source composed of glucose and polyvinyl alcohol, the D10 decreased from 0.67 μm to 0.49 μm, and the powder compaction density decreased to 2.63 g / cm³. 3 This indicates that applying the same degree of grain growth restriction to the second ferric phosphate as to the first ferric phosphate increases the proportion of fine particles, which is not conducive to the effective stacking of particles.
[0118] Compared with Comparative Example 3, in Example 2, by reversing the correspondence between the first and second carbon sources and the first and second iron phosphates, D10 decreased to 0.41 μm, while D90 increased to 6.18 μm, and the powder compaction density decreased to 2.58 g / cm³. 3 The results indicate that ferric phosphate exhibits a strong grain growth trend when polyvinyl alcohol is lacking, while ferric phosphate shows insufficient grain growth when polyvinyl alcohol is restricted, resulting in a simultaneous expansion of the particle size distribution towards both the coarse and fine ends.
[0119] Compared with Comparative Example 4, in Example 2, after mixing the first precursor slurry and the second precursor slurry and then spray-drying them together, the powder compaction density increased from 2.74 g / cm³. 3 Reduced to 2.66 g / cm³ 3 This indicates that separate spray drying is beneficial for maintaining the local correspondence between the first ferric phosphate and the first carbon source, as well as between the second ferric phosphate and the second carbon source.
[0120] In Comparative Example 5, after removing polyvinyl alcohol from the first carbon source, D90 increased to 5.82 μm; in Comparative Example 6, after increasing the proportion of polyvinyl alcohol in the first carbon source, D10 decreased to 0.46 μm. This indicates that the restriction on grain growth of ferric phosphate should neither be completely eliminated nor excessively strengthened.
[0121] Test Example 2 The carbon content in the high-pressure lithium iron phosphate cathode materials obtained in Examples 1 to 5 and Comparative Examples 1 to 6 was tested using high-frequency infrared carbon-sulfur analysis. Each sample was tested in parallel three times and the average value was taken.
[0122] The test results are shown in Table 2.
[0123] Table 2. Carbon content test results for each embodiment and comparative example.
[0124] As shown in Table 2, the final carbon content of the high-compact lithium iron phosphate cathode materials obtained in Example 2 and Comparative Examples 1 to 4 are all at similar levels. However, as shown in Table 1, there are still significant differences in their particle size distribution and powder compaction density.
[0125] In particular, the carbon contents of Example 2 and Comparative Example 3 were 1.38 wt% and 1.37 wt%, respectively, which were basically at the same level, but their powder compaction densities were 2.74 g / cm³, respectively. 3 and 2.58 g / cm 3 Therefore, the high-pressure compaction effect obtained in this application is not solely due to increasing the final carbon content, but is related to the directional correspondence between the first ferric phosphate, the second ferric phosphate, the first carbon source, and the second carbon source, as well as the respective spray drying treatment methods.
[0126] Test Example 3 The high-pressure lithium iron phosphate cathode materials obtained in Examples 1 to 5 and Comparative Examples 1 to 6 were respectively prepared into cathode sheets and assembled into CR2032 coin cells.
[0127] High-pressure lithium iron phosphate cathode material, conductive carbon black SP and polyvinylidene fluoride are mixed in a mass ratio of 95:2.5:2.5, and N-methylpyrrolidone is used as a solvent to prepare cathode slurry. The cathode slurry is coated on the surface of aluminum foil, and the cathode sheet is obtained after vacuum drying, rolling and stamping.
[0128] Each group of positive electrode sheets used the same active material areal density and the same rolling conditions. Lithium metal sheets were used as the negative electrode, and the same separator and electrolyte were used. CR2032 coin cells were assembled in an argon-filled glove box.
[0129] The battery was tested at 25°C, with a charge / discharge voltage range of 2.5–3.65 V. First, an initial charge / discharge test was performed at 0.1C, and the initial discharge specific capacity at 0.1C was recorded. Subsequently, the discharge specific capacity at 1C and 3C was tested.
[0130] The test results are shown in Table 3 and Figure 3 .
[0131] Table 3. Electrochemical performance test results of each example and comparative example.
[0132] As shown in Tables 1 and 3, the initial discharge specific capacities at 0.1C for Example 2 and Comparative Example 1 are 161.9 mAh / g and 160.7 mAh / g, respectively, with only minor differences. However, the powder compaction density of Example 2 is significantly lower than that of Comparative Example 1 (2.61 g / cm³). 3 Increased to 2.74 g / cm³ 3Meanwhile, the 3C discharge specific capacity increased from 136.9 mAh / g to 140.7 mAh / g. This indicates that, under the differential regulation of the first and second carbon sources, the difference in specific surface area between the first and second iron phosphates can form a particle size distribution suitable for improving particle filling efficiency without causing significant capacity loss.
[0133] Compared to Comparative Example 2, Example 2 showed less change in the initial discharge specific capacity at 0.1C, but its powder compaction density decreased to 2.63 g / cm³. 3 The 3C discharge specific capacity decreased to 137.6 mAh / g. This result indicates that when the second ferric phosphate uses the same polyvinyl alcohol-containing carbon source as the first ferric phosphate, the second ferric phosphate is subject to additional grain growth limitations, which is not conducive to obtaining a particle distribution that balances powder compaction density and rate performance.
[0134] Compared with Comparative Example 3, under the condition that the final carbon content is basically the same, the compacted density of the powder in Comparative Example 3 is 2.74 g / cm³. 3 Reduced to 2.58 g / cm³ 3 The specific capacity at 0.1C initial discharge decreased from 161.9 mAh / g to 157.4 mAh / g, at 1C discharge it decreased from 152.3 mAh / g to 144.6 mAh / g, and at 3C it decreased from 140.7 mAh / g to 128.7 mAh / g. This result indicates that there is a directional matching relationship between the first and second carbon sources and the first and second iron phosphates, and they cannot be arbitrarily interchanged.
[0135] Among them, the first ferric phosphate, with its higher specific surface area, exhibits a stronger grain growth tendency, requiring targeted restriction using polyvinyl alcohol in the first carbon source; the second ferric phosphate, with its lower specific surface area, shows a relatively weaker grain growth tendency, and only glucose is used as the second carbon source to avoid imposing the same degree of grain growth restriction on it. Through the above-mentioned reverse compensation, controlled particle size differentiation is achieved between the first and second ferric phosphates during the joint high-temperature sintering process.
[0136] Compared with Comparative Example 4, Example 2 showed that spray drying followed by mixing resulted in a powder compaction density of 2.66 g / cm³. 3 Increased to 2.74 g / cm³ 3 Meanwhile, the 3C discharge specific capacity increased from 135.8 mAh / g to 140.7 mAh / g, further demonstrating that separate spray drying can maintain the local correspondence between the first iron phosphate and the first carbon source, as well as between the second iron phosphate and the second carbon source, before joint high-temperature sintering.
[0137] Compared to Comparative Example 5, in Example 2, removing polyvinyl alcohol from the first carbon source resulted in a decrease in powder compaction density and discharge specific capacity at all rates. Compared to Comparative Example 6, excessively increasing the polyvinyl alcohol content also led to a decrease in powder compaction density and 3C discharge specific capacity. This demonstrates that the first carbon source has a suitable range for regulating the growth trend of the first iron phosphate grains, and a higher polyvinyl alcohol content is not necessarily more beneficial.
[0138] Based on the test results in Tables 1 to 3, it can be seen that by making the specific surface area of the first type of iron phosphate higher than that of the second type of iron phosphate, and by using the first carbon source composed of glucose and polyvinyl alcohol to correspond to the first type of iron phosphate and glucose as the second carbon source to correspond to the second type of iron phosphate, and by spray drying the first and second precursor slurries respectively, as well as the subsequent low-temperature carbonization stage and high-temperature sintering stage, the different grain growth trends of the two types of iron phosphate can be differentially regulated. This reduces the formation of abnormal coarse particles and excessively fine particles, while increasing the powder compaction density of the high-compact lithium iron phosphate cathode material and maintaining its capacity utilization and rate performance.
[0139] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-pressure lithium iron phosphate cathode material, characterized in that, Includes the following steps: S1 uses a specific surface area of 12.0–18.0 m². 2 / g of primary ferric phosphate and a specific surface area of 4.0–8.0 m² 2 / g of second iron phosphate; the first carbon source is composed of glucose and polyvinyl alcohol, and the second carbon source is glucose; The first ferric phosphate and the polyvinyl alcohol were premixed and then added to a lithium source and glucose from the first carbon source. The mixture was then wet-milled to obtain a first precursor slurry. The second iron phosphate, lithium source, second carbon source and deionized water are mixed and wet milled to obtain a second precursor slurry. The median particle size difference between the first precursor slurry and the second precursor slurry is not greater than 0.04 μm. S2, the first precursor slurry and the second precursor slurry are spray-dried respectively to obtain the first spray precursor and the second spray precursor; S3, the first spray precursor and the second spray precursor are mixed to obtain a mixed precursor. Under nitrogen protection, the mixed precursor is subjected to a low-temperature carbonization stage and a high-temperature sintering stage in sequence. The temperature of the low-temperature carbonization stage is 400-450°C, and the temperature of the high-temperature sintering stage is 740-770°C. After cooling, the high-pressure lithium iron phosphate cathode material is obtained.
2. The method for preparing high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that, The Fe / P molar ratio of both the first and second iron phosphates is 0.995–1.005, and the median particle size of both raw materials is 0.8–1.8 μm.
3. The method for preparing high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that, The mass ratio of glucose to polyvinyl alcohol in the first carbon source is 65:35 to 80:20, the amount of the first carbon source added is 6.0% to 8.0% of the mass of the first iron phosphate, and the amount of the second carbon source added is 6.0% to 8.0% of the mass of the second iron phosphate.
4. The method for preparing high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that, The lithium source is lithium carbonate, and the Li / Fe molar ratio in the first precursor slurry and the second precursor slurry is 1.02 to 1.
05.
5. The method for preparing high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that, The median particle size of both the first precursor slurry and the second precursor slurry is 0.30–0.40 μm.
6. The method for preparing high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that, The degree of alcoholysis of the polyvinyl alcohol is 87-89 mol%, and the degree of polymerization is 1600-1800.
7. The method for preparing high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that, The inlet air temperature of the spray dryer is 210-240℃, and the outlet air temperature is 90-110℃; based on the mass of iron phosphate contained, the mass ratio of the first spray precursor to the second spray precursor is 55:45-65:
35.
8. The method for preparing high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that, The low-temperature carbonization stage lasts for 2–4 hours, and the high-temperature sintering stage lasts for 7–10 hours.
9. The method for preparing high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that, After the high-temperature sintering stage is completed, the material is cooled under nitrogen protection, and then subjected to airflow pulverization and sieving.
10. A high-pressure lithium iron phosphate cathode material, characterized in that, The high-compact lithium iron phosphate cathode material has a D10 of 0.61–0.68 μm, a median particle size of 1.68–1.90 μm, a D90 of 4.50–5.14 μm, and a carbon content of 1.31–1.46 wt%. The powder compaction density, measured under 100 MPa pressure for 10 s, is 2.69–2.74 g / cm³. 3 .